Fake or not fake? : Perceptions of undergraduates on (dis)information and critical thinking - Melro, Ana (Array, 2019)
In an increasingly challenging media environment of post-truth and fake news, disinformation may impact the way young people perceive the world. In this study, we seek to understand how young people engage with news, their perceptions around disinformation, and how they see the relevance of critical thinking for their civic and political lives. Using a mixed method model, we developed a focus group activity with a total of 45 participants, based on the analysis of 562 questionnaires previously administered to first-year undergraduates of two Portuguese universities. The results show that although most students report limited critical analysis of information, they do reveal concerns about disinformation in their lives, suggesting a set of actions in order to combat fake news spread. Furthermore, the findings reinforce the need for news and media literacy that concerns a post-fact culture.